Effects of fungicides and plant extracts on seed germination and seed associated mycoflora of Lens arietinum L. and Lathyrus sativus (Journal of Bio-Science, 2016)
Contexts: seed treatment reduced seed mycoflora. Evidences revealed that chemical fungicides and plant extracts were effectively controlled seed mycoflora and enhanced seed germination of pulse crops.Objectives: To determine the effects of chemical fungicides and plant extracts on seed germination and seed associated mycoflora on Lens arietinum L. (lentil) and Lathyrus sativus (khesari).Materials and Methods: All the samples were collected Rajshahi region during June - August 2012. The detection of seed mycoflora, seed germination and seed treatment with fungicides and plant extracts were carried out by using the blotter test (ISTA-1966).Results: Seed germination percentage was significantly (p?0.05) increased with both the treatments. Captan (1.2%) was more effective in comparison with Dithane M-45 (1.4%) and seed germination (%) was gradually increased with increase of the doses of fungicides. Seed associated mycoflora also significantly (p?0.05) varied with the treatments. Aspergillus flavus was the most dominant fungi in lentil and Fusarium oxysporum was in khesari for both the treatments and control. No fungi were recorded at 1.2 and1.4% doses of Captan and Dithane M-45 treated seeds of both pulses. Plant extracts increased germination percentage over control and showed different levels of antifungal activity against seed associated mycoflora (SAM) of both pulse seeds. Among the extracts, Allium sativum showed promising result in controlling of SAM of lentil and khesari. Besides this, A. flavus was remarkably eliminated with the all types of used extracts.Conclusion: From this study it had been clearly found that seed treatment with chemical fungicides and plant extracts were controlled seed mycoflora of lentil and khesari and increased seed germination.J. bio-sci. 22: 101-110, 2014